Morphological and textural evolution of the prismatic ultrastructure in mollusc shells: A comparative study of Pinnidae species. (February 2019) - Reich, Elke; Schoeppler, Vanessa; Lemanis, Robert; Lakin, Evgeny; Zolotoyabko, Emil; Zöllner, Dana; Zlotnikov, Igor
Graphical abstract: Abstract: Molluscan shells, exhibiting a variety of complex three-dimensional architectures, are an exemplar model system to study biogenic mineral formation by living organisms. Recent studies have demonstrated that the deposition process of some shell ultrastructures can be described using classical analytical models borrowed from materials physics, which were developed to predict the structural evolution of man-made and geological polycrystalline composite assemblies. In the current study, we use this newly developed capacity to quantitatively describe the morphogenesis of the prismatic ultrastructure in three shells from the bivalve family Pinnidae towards establishing a correlation between structure, texture, growth kinetics, topology and phylogeny of the species. Using data collected by electron microscopy, synchrotron-based microtomography, electron backscatter diffraction analysis (EBSD) and X-ray diffraction we demonstrate that the prismatic ultrastructures in Pinnidae are formed following either ideal or triple-junction-controlled kinetics, which are shown to be closely linked to the morphological and topological characteristics, as well as crystallographic texture of these biocomposites. The experimental and analytical framework presented in this comparative study can serve as an additional tool for classifying molluscan shell ultrastructures on the levels of structural and textural morphogenesis. Statement of Significance: The ability to quantitatively describe the structural evolution of the prismatic architecture in mollusc shells is used for the first time to derive and compare between analytical parameters that define the growth kinetics and morphological and topological evolution during the growth of three shells from the family Pinnidae from two different genera. Furthermore, these parameters are linked to the evolution of crystallographic texture in the studied architectures. The developed experimental and analytical framework not only enables us to quantitatively describe species-specific growth mechanisms but also suggests a direct correlation between the evolution of morphology and texture.